1996
DOI: 10.1007/s001090050076
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin structure and the regulation of gene expression: remodeling at the MMTV promoter

Abstract: The role of the various levels of chromatin organization in the control of eukaryotic gene expression is discussed on the basis of recent advances in our understanding of chromatin structure in well-defined model systems. Particular attention is devoted to the precise structure and the possible functions of positioned nucleosomes and to the enzymatic mechanism of nucleosome remodeling. Some of the principles involved are illustrated with genomic footprinting results obtained with the mouse mammary tumor virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 143 publications
1
32
0
Order By: Relevance
“…The best-studied chromatin model in which NFI proteins function is the MMTV promoter. Initial studies indicated that the nucleosome phasing was sequencedependent (11), although more recent work has suggested that both NFI and glucocorticoid receptor (GR) binding may influence the MMTV-promoter chromatin structure (27). One widely supported model for hormone-induction of MMTV transcription is that NFI binding is normally excluded from the MMTV promoter by the presence of a sequence-dependent phased nucleosome (28), and that GR-recruited chromatin remodeling allows NFI to bind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best-studied chromatin model in which NFI proteins function is the MMTV promoter. Initial studies indicated that the nucleosome phasing was sequencedependent (11), although more recent work has suggested that both NFI and glucocorticoid receptor (GR) binding may influence the MMTV-promoter chromatin structure (27). One widely supported model for hormone-induction of MMTV transcription is that NFI binding is normally excluded from the MMTV promoter by the presence of a sequence-dependent phased nucleosome (28), and that GR-recruited chromatin remodeling allows NFI to bind.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of NFI-binding specificity used direct affinity isolation of transcription factor binding sites from the human genome (8), selection on oligonucleotide libraries (9), or bioinformatic comparison of motifs held in common by the promoters of putative NFI-regulated genes (10). NFI proteins have been linked to chromatin because both NFI and glucocorticoid receptor (GR) binding influence mouse mammary tumor virus (MMTV) promoter chromatin structure (11), and NFI proteins have functional and physical interactions with histones H1 and H3 (12,13).…”
mentioning
confidence: 99%
“…The chromatin structure of the ORF was the same under repressing and activating conditions (2). Removal of promoter nucleosomes is presumed to relieve the repression brought about through their interference with the transcription machinery (5,6) and may be a general feature of eukaryotic genes (7)(8)(9)(10).…”
mentioning
confidence: 89%
“…20 Specifically, CMV promoter as well as simian virus 40 (SV40) or rous sarcoma (RSV) promoters may be silenced by the action of cytokines produced by infected cells. 3 However, recent evidence indicates that HDAC inhibitors may strongly activate a chromatin integrated viral promoter 21 and it is possible that this mechanism may be exploited to reactivate a silenced viral promoter. This issue was addressed in the experiments described below.…”
Section: Ra and Tsa Effects On Transgene Expression In Vivomentioning
confidence: 99%